The Effect of Cooling Pad Spacing in Closed Cages on Broiler Chicken Performance - Fitri , Khayla Nur Aisya; Mulyono, Ali Mursyid Wahyu; Husein, Muhammad (Jurnal Biologi Tropis, 2026)
Optimizing cooling pad placement in closed house systems is critical to ensuring uniform thermal distribution and preventing heat stress, yet the effect of cooling pad distance on broiler performance during the starter phase remains insufficiently studied. Objective: This study investigated the effect of three cooling pad distances (6 m, 12 m, and 18 m) on feed intake (FI), body weight gain (BWG), and feed conversion ratio (FCR) of broiler chickens during the starter phase. Methods: A completely randomized design (CRD) was applied with three treatments (P1, P2, P3) and four replications (5 birds/replication; 60 birds total) over 14 days at a commercial broiler farm in Jenawi, Karanganyar. Data were analyzed using one-way ANOVA and Duncan's Multiple Range Test. Results: Cooling pad distance had no significant effect (P>0.05) on FI, BWG, or FCR, with all FCR values remaining within the normal commercial range. The evaporative cooling pad effectively distributed cool air uniformly up to 18 m, demonstrating that the full capacity of the closed house can be utilized without compromising production efficiency. These findings contribute scientific evidence that proper cooling pad installation eliminates thermal gradients across house zones, providing a basis for optimizing housing design and management in tropical broiler production.